CHEMISTRY, SMALL-SCALE INHOMOGENEITY, AND FORMATION OF MOLDAVITES AS CONDENSATES FROM SANDS VAPORIZED BY THE RIES IMPACT - von Engelhardt W.; Berthold C.; Wenzel T.; Dehner T. (My University, 2005)
The formation of the Ries impact and the moldavites have identical radiogenic ages of 14.3 Ma. According to this conformity in age moldavites are generally regarded as products of the Ries impact. This paper, which is divided into two sections, deals with two aspects of the moldavite-forming process: the formation of moldavite bodies by accretion of small precursors, and the physical and chemical conditions under which these primary units originated from sands which covered the Ries impact site.